THE MACEDONIANSHIP AS A SYMBOL OF BUILDING (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
This text is related to the newest book of Stefan Vlahov-Micov „Creative reach in the Macedonian spirit“which offers a newest, systematic and well-argued pursuit of the Macedonian literature and culture. The paperwork is not a dry presentation of the attitudes expressed in this book, but is a serious pursuit, affirmation, and also a mild dispute with some of his thoughts connected with the newer Macedonian literature-critical idea.